2015
DOI: 10.3389/fnagi.2015.00201
|View full text |Cite
|
Sign up to set email alerts
|

Older adults can improve compensatory stepping with repeated postural perturbations

Abstract: The ability to respond quickly and accurately to an external perturbation with a stepping response is critical to avoid falls and this ability is impaired in older, compared to young adults. However, little is known about whether young and older adults improve compensatory stepping responses similarly with practice. This study compares the extent to which young and older adults can improve, retain, and generalize postural compensatory steps in response to external perturbations. Centre of mass displacement, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 23 publications
6
70
0
2
Order By: Relevance
“…Another study applied only perturbations leading to a forward loss of balance,32 whereas three studies applied perturbations in both directions 34, 35, 36. Although the impact of perturbation direction on falls incidence or types of falls experienced is not known, there is evidence to suggest that adaptation to perturbations in one direction might not transfer and benefit reactive balance control in another direction 27, 38. Perturbations in the mediolateral directions should also be considered when applying PBT in clinical settings, because of the reduced mediolateral stability seen in older adults 51.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study applied only perturbations leading to a forward loss of balance,32 whereas three studies applied perturbations in both directions 34, 35, 36. Although the impact of perturbation direction on falls incidence or types of falls experienced is not known, there is evidence to suggest that adaptation to perturbations in one direction might not transfer and benefit reactive balance control in another direction 27, 38. Perturbations in the mediolateral directions should also be considered when applying PBT in clinical settings, because of the reduced mediolateral stability seen in older adults 51.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the diminished reactive gait stability seen in older adults in response to a novel perturbation compared with young adults,25 reactive locomotor adaptation potential (the ability to adapt and improve reactive gait adjustments in a feedback‐driven manner) does not appear to decline with age,26, 27 nor does it appear to be specific to one mode (stance, sit‐to‐stand or gait) of locomotion 28. By capitalizing on older adults’ potential for improvement by providing sufficient and specific stimuli (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the findings indicated that although reduced stability at first foot contact could be a determinant of taking additional steps, stepping responses could also be attributable to the COM motion state as early as first step lift-off, preceding foot contact. Since perturbation training has been reported to improve the reactive control of balance stability (Barrett et al, 2012; Dijkstra et al, 2015; Kurz et al, 2016; Mansfield et al, 2015; Pai et al, 2014; Rosenblatt et al, 2013), which increased balance stability at the instant of step lift-off (Lee et al, 2016; Liu et al, 2016), perturbation-based training interventions aimed at improving the reactive control of stability would reduce initial balance instability at first step lift-off and possibly the consequent need for multiple steps in response to balance perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…HO participants were similar with respect to age, Montreal Cognitive Assessment, and MiniBESTest to the PD participants (Table 1). Data from HO subjects have been compared to younger adults previously [9]. All participants provided informed consent, and the research protocol was approved by the OHSU institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…This protocol has been described previously [9]. Briefly, participants completed two visits on consecutive days.…”
Section: Methodsmentioning
confidence: 99%